Apiaries of Brazil – a bibliographic survey on Brazilian apiaries through the atlas of Brazilian beekeeping - Lima Neto, Inácio Alves de (Brazilian Journal of Production Engineering, 2025)
Bees play an important role in the ecosystem, being responsible for pollinating flowers that later become fruits and vegetables, contributing to the preservation of plant species. In the production sphere, bees play a fundamental role in the economy with their main product, honey. In 2020, Brazil reached 10th place in honey production with 51 thousand tons, generating R$ 957.8 thousand reais in the same year. However, even with the increase in honey production, there was a drop in the export of the product in recent years, directly harming the economy. Based on this, the study in question sought, through bibliographic research, using as its main basis the Atlas of Beekeeping in Brazil, developed by the Brazilian Association of Bee Studies, to map Brazilian apiaries, as well as collect data on the production and export of honey in the last 10 years, discussing the importance of beekeeping for nature and the contribution of honey production to the economy. At the end of the research, it was concluded that Brazil has around 101 thousand registered apiaries, spread throughout the territory, moving around R$ 957.8 thousand reais in honey production, with the South Region as a pioneer in beekeeping and honey production.
Keywords: Apiaries; Bees; Honey